Duplication and Losses of Opsin Genes in Lophotrochozoan Evolution. (22nd March 2023) - De Vivo, Giacinto; Crocetta, Fabio; Ferretti, Miriam; Feuda, Roberto; D'Aniello, Salvatore
Abstract: Opsins are G-coupled receptors playing a key role in metazoan visual processes. While many studies enriched our understanding of opsin diversity in several animal clades, the opsin evolution in Lophotrochozoa, one of the major metazoan groups, remains poorly understood. Using recently developed phylogenetic approaches, we investigated the opsin evolution in 74 lophotrochozoan genomes. We found that the common ancestor of Lophotrochozoa possessed at least seven opsin paralog groups that underwent divergent evolutionary history in the different phyla. Furthermore, we showed for the first time opsin-related molecules in Bilateria that we named pseudopsins, which may prove critical in uncovering opsin evolution.